Maintenance management performance – An overview towards evaluating Malaysian palm oil mill - Baluch, Nazim Hussain; Abdullah, Che Sobry; Mohtar, Shahimi (Institut Teknologi Bandung, 2010)
Deficient maintenance management can severely affect competitiveness of an organization by reducing throughput, increasing inventory, and leading to poor performance.Performance cannot be managed without measurement: it provides the required information to the management for effective decision making; and is used by industries to assess progress against set goals and objectives in a quantifiable way for effectiveness and efficiency.For the palm oil mills to stay competitive, it is imperative that they elevate the maintenance management role; from a cost center to the strategic partner in business.This paper highlights how measuring maintenance performance helps us identify the factors causing poor performance, and provides an opportunity to improve company’s profits.